ANIMATION: A LEARNING TOOL - Shedge Vishakha S; Mandhare Yogendra S (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Childhood has changed rapidly over the past few years and the methods that we use as teachers and educators of children and young people should reflect these changes. Children learn best and most when they enjoy what they are doing. Using animation as a tool to encourage and develop children’s learning is not only fun but effective! Use of animation in special education has gained great attention recently. Therefore, the use of animation for helping individuals with special needs has become an important research question and this study aims to examine and discuss the role of using animation as a tool to enhance learning of individuals with special needs. This is a qualitative study in which document analysis was used to collect the data. Results revealed the trends in using animation in education and the benefits of animation for enhancing learning of individuals with special needs. This study tried to provide a comprehensive review on the effectiveness of using animation in education and discussed the existing and possible benefits of using animation for individuals with special needs. Results are discussed with relevant literature and recommendations for further research and practices are presented in the study.